Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2015
DOI: 10.1080/17429145.2015.1052026
|View full text |Cite
|
Sign up to set email alerts
|

The effects of soil metals on the composition of oil ofPaeonia ostiiseeds

Abstract: Peony seed oil has been known to have a high value for health due to the high content of unsaturated fatty acid. However, few studies have investigated which factors impact the oil quality and composition of seeds in the traditional mining cultivation area. In the present study, the investigation was conducted in 30 cultural field sites. Significantly negative relationships were found between Cu content in soils or leaves and linoleic and unsaturated fatty acids. Further tests revealed that Cu evidently accumu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 30 publications
0
6
0
Order By: Relevance
“…The influence of minerals on the stability and content of unsaturated acids in medicinal plants and oils is mentioned in the literature. Zhang et al [56] reported a significant decrease in the content of unsaturated C18 acids with low unsaturation degree in the oil of Paeonia ostii seeds as the content of Cu 2+ increases in the soil, but especially as result of accumulation in the plant. This is explained by the prooxidative character of Cu 2+ on unsaturated FAs with a significant positive correlation between peroxides of linoleic and linolenic acids and Cu in plant.…”
Section: Antioxidant Capacity Polyphenol and Carotenoid Profilesmentioning
confidence: 99%
“…The influence of minerals on the stability and content of unsaturated acids in medicinal plants and oils is mentioned in the literature. Zhang et al [56] reported a significant decrease in the content of unsaturated C18 acids with low unsaturation degree in the oil of Paeonia ostii seeds as the content of Cu 2+ increases in the soil, but especially as result of accumulation in the plant. This is explained by the prooxidative character of Cu 2+ on unsaturated FAs with a significant positive correlation between peroxides of linoleic and linolenic acids and Cu in plant.…”
Section: Antioxidant Capacity Polyphenol and Carotenoid Profilesmentioning
confidence: 99%
“…The earlier mentioned results showed that the seven oligostilbenes were the majority of the total oligostilbenes, and could be used to evaluate the content of the main oligostilbenes in the seed shell of P. ostii . Oligostilbenes were considered to be the characteristic component in the seed shell of genus Paeonia with a wide range of biological activities . Therefore, for the first time the content of the seven oligostilbenes in the seed shell of P. ostii were simultaneously determined in this study.…”
Section: Resultsmentioning
confidence: 99%
“…Oil tree peony is a new type of tree peony cultivar where the seed kernels can be used for the preparation of edible oil, and P. ostii or P. rockii are the only two oil peony cultivars authorised by the Ministry of Health of the People's Republic of China in March 2011 . The plantation area of oil tree peony is very large at present due to the high oil content (varies from 24.12% to 37.83%) in peony seed kernels and the high unsaturated fatty acid content (more than 90%) in peony seed oil …”
Section: Introductionmentioning
confidence: 99%
“…Plants growing in contaminated soils showed a decline in progress, enactment and harvest (El-Adawy and Taha 2001). Zhang et al (2015) observed those factors which can impact on the quality and composition of oil of peony seeds, cultivated in the traditional excavating agriculture area in 30 cultural field sites. They described considerably destructive relationships in between Cu content in soils or leaves and linoleic and unsaturated fatty acids.…”
Section: Introductionmentioning
confidence: 99%